American orientalism: A critical reading through Edgar Allan Poe - Loiy Hamidi Qutaish Alfawa’ra; Jameel Ahmed Alghaberi (Studies in English Language and Education, 2023)
To date, The Arabian Nights still create frames of reference outside its fictive core. The article critically examined the adaptations and appropriation of the classic Arabian Nights by Edgar Allan Poe and how he invested his interest in the Orient to advance his career as a writer. More specifically, the aim was to study the links between European Orientalism and the new version of the Orient constructed in the United States. Various modes of reading and approaches were used to critically interpret the primary texts. Orientalism and postcolonial theories provided a theoretical framework for the study, and the deconstructive approach was applied in certain contexts to deconstruct and dismantle the stereotyping and mythologizing of the Orient. The article contributed to the growing scholarship on American oriental discourse by offering a counter perspective. Poe’s poems and short stories all perpetuate negative oriental representations. His obsession with the Orient is not reflected as aesthetic appreciation but it is rather appropriation that distorts and never restores. Poe’s oriental discourse is only examined lately by Arab critics of American literature and more specifically it surfaced through translations of his works into Arabic. Through stereotypical duplication in the world of realism, a fake Orient has become there in the world of reality.